Assessing the Odds of Achieving the MDGs - Go, Delfin S. (The World Bank, 2011)
How many countries are on target to achieve the Millennium Development Goals by 2015? How many countries are off target, and how far are they from the goals? And what factors are essential for improving the odds that off-target countries can reach the goals? This paper examines these questions and takes a closer look at the diversity of country progress. The authors argue that the answers from the available data are surprisingly hopeful. In particular, two-thirds of developing countries are on target or close to being on target for all the Millennium Development Goals. Among developing countries that are falling short, the average gap of the top half is about 10 percent. For those countries that are on target, or close to it, solid economic growth and good policies and institutions have been the key factors in their success. With improved policies and faster growth, many countries that are close to becoming on target could still achieve the targets in 2015 or soon after